Strategies and Challenges in Preventing Money Politics in the 2024 Legislative Elections - Faiz Raudhin Zulfikar; Irsyaf Marsal (Law Development Journal, 2026)
This study aims to examine and analyze the strategies employed and the challenges faced by the election supervisory body in preventing money politics during the 2024 legislative elections. Utilizing an empirical legal research method, this study combines statutory, case, and conceptual approaches by conducting field observations, interviews, and document studies to analyze fundamental gaps between normative legal requirements and the practical implementation realities. The novelty of this study lies in its specific examination of how supervisory bodies have changed and adapted their responses to newly emerging forms of money politics, such as digital currency transfers, the distribution of discount vouchers, and disguised social assistance, accompanied by a quantitative assessment of resource disparities where a single district-level supervisory team may oversee an average of seventy polling stations. Based on this analysis, it is concluded that although the supervisory bodies have strong legal authority and have successfully integrated technologies such as the Siwaslu system for real-time monitoring and social media monitoring, their overall effectiveness is severely limited by structural constraints on human resources and the continuing evolution of money politics tactics. Furthermore, low public awareness regarding the legal implications of vote-buying continues to pose an obstacle to prevention efforts. Consequently, this study recommends strengthening the regulatory framework to impose stricter and more deterrent sanctions, increasing public participation through targeted youth engagement, and adopting risk-based monitoring strategies to maximize limited resources in historically vulnerable areas.